(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, which can attack the lungs and other organs. Pulmonary tuberculosis is still one of the world’s public health problems even though TB control efforts have been implemented in many countries since 1995. The target of the national pulmonary TB prevention program is eliminated in 2035 and Indonesia free from pulmonary TB in 2050. Purpose of Research, this is to find out the factors that influence the incidence of pulmonary tuberculosis in the Jati Health Center Area. This study uses secondary data taken from data from the Jati Health Center and the analysis in this study uses the CHAID Exhaustive method. The results of this study indicate that the number of pulmonary tuberculosis patients with a positive smear suspicion when viewed from the type of sufferers is mostly new cases as many as 216 people. Associated with the type of patient who came for treatment at the Teak Health Center, all patients seeking treatment received a cure category of 99.6% which is a new patient treatment category. So the factors that influence the incidence of pulmonary tuberculosis are the type of patient and treatment results.